Quasi‐Ordered Nanoforests with Hybrid Plasmon Resonances for Broadband Absorption and Photodetection (Adv. Funct. Mater. 38/2021). (16th September 2021) - Li, Mao; Shi, Meng; Wang, Bin; Zhang, Chenchen; Yang, Shuai; Yang, Yudong; Zhou, Na; Guo, Xin; Chen, Dapeng; Li, Shaojuan; Mao, Haiyang; Xiong, Jijun
Abstract : Quasi‐Ordered Nanoforests In article number 2102840, Shaojuan Li, Haiyang Mao, Jijun Xiong, and co‐workers propose a quasi‐ordered nanoforest‐based absorber with multi‐level hybridization of plasmon resonances and cavity mode resonances for broadband high absorption. The absorber shows independence of absorption properties on polarization and incident angle of light. By integrating the absorber onto a thermopile device, the device achieves a large enhancement in photoresponse, from 300 nm to 2500 nm, providing a prospect for diverse applications where effective light absorption is required.